2021
DOI: 10.1021/acs.analchem.1c01537
|View full text |Cite
|
Sign up to set email alerts
|

Ratio-Adjustable Upconversion Luminescence Nanoprobe for Ultrasensitive In Vitro Diagnostics

Abstract: Synthesis procedures of nanocrystals and NO recognition molecules, preparation of test paper, mass spectra, TEM images of the UCNPs, luminescence variations of the nanoprobes upon additions of different interference anion ions, and luminescent images of the test paper after exposure to different amounts of NO (PDF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…For example, the presence of an analyte can specifically induce the increase of one signal, followed by the decrease of the other, thereby establishing a substantial change in the ratio between these two detection signals. This approach allows tuning of both emission intensities (by adjusting excitation power) accessing even higher sensitivities 242 due to high signal to background ratio or simultaneous detection of two analytes. 243 Dual-emission RENPs are superior to many other photoluminescent nanoprobes that are based on two-dye embedded NPs, NP−dye nanoconjugates, or hybrid NPs due to preclusion of dye leakage, photobleaching, and possibly phototoxicity.…”
Section: Upconversion-based Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the presence of an analyte can specifically induce the increase of one signal, followed by the decrease of the other, thereby establishing a substantial change in the ratio between these two detection signals. This approach allows tuning of both emission intensities (by adjusting excitation power) accessing even higher sensitivities 242 due to high signal to background ratio or simultaneous detection of two analytes. 243 Dual-emission RENPs are superior to many other photoluminescent nanoprobes that are based on two-dye embedded NPs, NP−dye nanoconjugates, or hybrid NPs due to preclusion of dye leakage, photobleaching, and possibly phototoxicity.…”
Section: Upconversion-based Sensingmentioning
confidence: 99%
“…Recently, J. Zhou et al . designed NaErF 4 :Yb 3+ ,Tm 3+ @NaYF 4 :Yb 3+ @NaNdF 4 :Yb 3+ RENPs with two independent emissions intensities, individually modulated for ultrasensitive monitoring of exhaled NO, as a prognostic biomarker to indicate the clinical course of asthma . To achieve sensitive detection of breath volatile NO gas, rhodamine derivatives operating as recognition units were encapsulated into a mesoporous silica layer on the surface of the upconverting RENPs.…”
Section: Upconversion Luminescence For Biomedical Applicationsmentioning
confidence: 99%
“…Jiang et al reported on a chlorinated graphene FET and its application in monitoring of NO under specified physiological requirements [ 55 ]. To facilitate naked eye-based on-site detection, Zhou et al recently developed ratiometric fluorescent probes with distinctive color changes to monitor exhaled nitric oxide to indicate the clinical course of asthma [ 56 ]. The fluorescent nanoprobe was also integrated with smartphone analysis for rapid and sensitive detection of exhaled NO.…”
Section: Gas Monitoring For Medical Diagnosismentioning
confidence: 99%
“…The production of NH 3 in the human body is related to protein metabolism. Proteins are degraded into non-storable amino acids to be used or metabolized, which leads to the formation of NH 3 [ 38 , 56 ]. Ammonia (NH 3 ) itself is a toxic and irritating gas.…”
Section: Gas Monitoring For Medical Diagnosismentioning
confidence: 99%
“…Luminescence in the near-infrared (NIR) region ranging from 650 to 950 nm for the NIR-I window and 1000–1700 nm for the NIR-II window has attracted tremendous attention recently because of its advantages of a high signal-to-background ratio and optical resolution at a deeper penetration depth (ca. 1–20 mm) compared to emissions in visible (400–700 nm) windows owing to reduced photon scattering, absorption, and lower autofluorescence. Over the past decades, various lanthanide sensitizers have been developed to achieve NIR luminescence, including Tm 3+ (800 nm from the transition of 3 H 4 → 3 H 6 ), Yb 3+ (980 nm from the transition of 2 F 5/2 → 2 F 7/2 ), Nd 3+ (808 nm from the transition of 4 F 3/2 → 4 I 9/2 ), Er 3+ (1550 nm from the transition of 4 I 13/2 → 4 I 15/2 , 1525 nm, 4 I 13/2 → 4 I 15/2 , and 980 nm from the transition of 4 I 11/2 → 4 I 15/2 ), , and Ho 3+ (1180 nm from the transition of 5 I 6 → 5 I 8 , 755 nm from the transition of 5 S 2 , 5 f 4 → 5 I 7 ) . Among these lanthanide sensitizer ions, Er has been widely developed due to its wide emission band, but its application is limited due to its low absorption cross section which reduces the emission efficiency, and it generally requires a relatively complex structure to prevent cross-relaxation .…”
Section: Introductionmentioning
confidence: 99%